Numerical simulation for train–track–bridge dynamic interaction considering damage constitutive relation of concrete tracks - Xu, Lei; Yu, Zhiwu; Shan, Zhi (Archives of Civil and Mechanical Engineering, 2021)
In this work, a novel and practical method is developed to depict the track slab damage and residual strain evolution, where the concrete damage constitutive relation of track slabs is considered within the train–track–bridge dynamics framework. A three-step strain method is presented to judge the load/unloading, compression/tension status of track slab elements ergodically, so that the damage condition and residual strain of track slabs can be determined. To improve the computational accuracy and efficiency, the combination of the matrix augment method and iterative solution algorithm is elucidated in detail. To validate the present model, the solutions among incremental solution, iterative solution, and non-iterative solution are firstly illustrated, and then experimental studies are performed to declare the effectiveness of this model in characterising strain/stress relation of concrete no matter in compression state or in tension state, and finally, other model results are also introduced to prove the effectiveness of this model. In the numerical studies, the damage distributions of track slabs in the longitudinal and lateral direction are presented, where the influence of track irregularities and track slab positions on the bridge is clarified, besides, the evolution of the damage and residual strain of a track slab subject to a moving train is revealed.